BIOMECHANICAL SIMULATION OF RADIAL HEAD SUBLUXATION IN CADAVERIC PEDIATRIC ELBOWS. Issue 7 (30th July 2021) - Meadows, Molly; Vuong, Brian; Storaci, Hunter; Tam, Kaysie; Shea, Kevin
Background: Radial head subluxation, known as pulled elbow or Nursemaid's elbow, is a common pediatric condition that occurs when a longitudinal traction force is applied to an elbow that is pronated and extended. Although the stability of the proximal radioulnar joint has been previously examined in cadaveric models, there are no current studies quantifying the biomechanics of nursemaid's elbow. The purpose of our study was to demonstrate and quantify the axial traction force required to produce a nursemaid's elbow in a pediatric cadaver specimen. Methods: Two fresh-frozen cadaveric elbows from a single 3 year-old male donor were dissected by a fellowship-trained orthopedic surgeon. An Instron 5944 testing machine with a 2 kN load cell was used to perform uniaxial testing. The radius and humerus were mounted to the Instron machine, and loaded in the axial direction with the elbow in full extension. Loading occurred at a rate of 10 mm/sec for 4 seconds, during which the force and actuator displacement were continuously recorded. The local instantaneous load and extension displacement at the time of subluxation were recorded, and data was synced with high-frame-rate video footage used to confirm the annular ligament subluxation. Results: The load to failure required to produce the nursemaid's elbow injury in the first elbow was 31N, with a failure displacement of 4.6mm. The second elbow demonstrated a load to failure of 26N, with a failure displacement of 4.6mm. After subluxation, we reduced the annular ligament from the first specimen. The elbow was then re-tested and demonstrated a load to failure of 20N, with a failure displacement of 2.6mm. Conclusion: Axial traction applied to a pediatric cadaver specimen results in subluxation of the annular ligament into the radiocapitellar joint. The mean load to failure is 28.5N, and a lower load to failure was required to produce a recurrent subluxation in a previously injured specimen. Lower load for a recurrent subluxation may be attributed to damage on the annular ligament due to the first subluxation. : Figure 1. Red arrows mark the proximal edge of the radial head before (A) and after (B) subluxation due to applied axial force.